Three Year Prognosis of Patients with Myocardial Infarction Depending on the Body Weight Index: Data of the Kemerovo Acute Coronary Syndrome Registry - D. Yu. Sedykh; A. I. German; O. N. Hryachkova; V. V. Kashtalap; O. L. Barbarash (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of body mass index (BMI) on the 3-year prognosis of patients after myocardial infarction (MI).Material and methods. The study is based on data from a 3-year observation of patients with MI from the Kemerovo registry of acute coronary syndrome (n=1366). The characteristics of patients with MI, distributed by the BMI, were determined, the outcomes were analyzed, the risk factors and predictors for the vascular events and mortality were identified.Results. Obesity was detected in 32.2% people with MI (I degree – 22.3%; II – 7.7%; III – 2.3%), lack of BMI at 0.5%, normal BMI at 20.5%, overweight at 46.9%. Patients with different BMI showed a comparable incidence of recurring MI. In patients with normal BMI, when compared with patients with obesity, unstable angina pectoris (UA), heart failure (HF) and strokes developed often. In patients with normal BMI compared with obese patients, fewer deaths from all causes were recorded within 3 years after MI. A similar pattern with respect to the group with normal BMI in terms of high overall mortality was obtained among patients with overweight who had a lower UA. Patients with obesity was favorable in relation to the development of HF, strokes and overall mortality than patients with overweight. Differences in the 3-year outcomes in the group of patients with MI and underweight were not found when compared with patients with normal and overweight, however, they had a higher of strokes compared with patients with obesity. At patients with I degree obesity within 3 years after MI UA, HF, strokes were less. Patients with III degree obesity, the maximum frequency of total mortality was recorded. The development of death from all causes during the observation period in patients with MI and obesity was associated with: male, smoking, multivessel arterial diseases, non-endovascular reperfusion, acute HF with MI, history of vascular events and angina pectoris; whereas with overweight: multifocal atherosclerosis and arterial hypertension; with a deficit of BMI: non-reperfusion; with normal BMI: heredity for cardiovascular diseases, dyslipidemia and atrial fibrillation.Conclusion. 3 years after MI patients with obesity of the I degree are less likely than patients with obesity of II-III deaths from all causes are recorded; these patients are less likely than patients with normal weight to develop strokes, HF, UA. Thus, patients with MI and the presence of I degree obesity are characterized by better survival during 3 years of observation.